Bioinspired Development of an In Vitro Engineered Fracture Callus for the Treatment of Critical Long Bone Defects. (15th August 2021) - Bolander, Johanna; Mota, Carlos; Ooi, Huey Wen; Agten, Hannah; Baker, Matthew B.; Moroni, Lorenzo; Luyten, Frank P.
Abstract: Cell‐based regenerative constructs provide hope for the restoration of tissue function in compromised biological conditions such as complex bone defects. A strategy mimicking the cascade of events of postnatal fracture healing suggests an implant design where progenitor cells provide the driving force for the construct's tissue forming capacity, while framing biomaterials provide cells with 3D cues to direct cellular processes. Large bone defects mainly heal through the formation of an intermediate endochondral fracture callus. The authors aimed to develop an in vitro engineered fracture callus manufactured by bioprinting to provide a spatially organized tissue construct based on: i) in vitro 3D primed human periosteum derived cells and ii) biocompatible thiol‐ene alginate hydrogels, mimicking the cells and extracellular matrix present in the different zones of the callus. Cell viability and maintained osteochondrogenic differentiation upon bioprinting is confirmed in vitro. In vivo assessment displays that the developed biomaterials provided essential 3D cues that further guided the cells in their tissue forming process in the absence of additional stimulatory molecules. The reported findings confirm the appeal of a biomimetic approach to steer tissue development of in vitro engineered constructs and illustrate the suitability of bioprinting methodologies for the fabrication of living regenerative implants. Abstract : A bioprinted fracture callus is developed based on primed cellular aggregates mimicking cells in the native callus. The aggregates form their specific extracellular matrix and are encapsulated in a hydrogel system matching the stiffness of the callus matrix. The hierarchical structure of the implant steers tissue development in vivo through paracrine signaling and the mechanical stimulation of the biomaterial.